1998
DOI: 10.1016/s0014-5793(98)00395-0
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of F1‐ATPase activity from Escherichia coli subunits α, β and subunit γ tagged with six histidine residues at the C‐terminus

Abstract: An engineered Q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The fact that the biomass yield decreased in combination with the reduction in the intracellular energy level is therefore a strong indication that an uncoupled ATPase is active in vivo, as recently found for E. coli (26). Our results are also in agreement with early reconstitution experiments, in which complexes of ␣, ␥, and ␤ (9,10,11), Bacillus strain PS3 (46), and Salmonella enterica serovar Typhimurium (19) were found to have high ATPase activities. The reduction in the intracellular energy level with an increased level of uncoupled F 1 -ATPase did not result in a shift of metabolism from homolactic fermentation to a mixed-acid pattern that would otherwise have provided the cell with extra ATP (14,43).…”
Section: Discussionsupporting
confidence: 92%
“…The fact that the biomass yield decreased in combination with the reduction in the intracellular energy level is therefore a strong indication that an uncoupled ATPase is active in vivo, as recently found for E. coli (26). Our results are also in agreement with early reconstitution experiments, in which complexes of ␣, ␥, and ␤ (9,10,11), Bacillus strain PS3 (46), and Salmonella enterica serovar Typhimurium (19) were found to have high ATPase activities. The reduction in the intracellular energy level with an increased level of uncoupled F 1 -ATPase did not result in a shift of metabolism from homolactic fermentation to a mixed-acid pattern that would otherwise have provided the cell with extra ATP (14,43).…”
Section: Discussionsupporting
confidence: 92%
“…Polyclonal Antibodies for Nha1p or Cos3p-His 6 -tagged Nha1p (C1ϩC2) (Nha1p (C1ϩC2)-His) bearing the Nha1p amino acid residues 434 -523 and the MBP-Cos3p-loop fusion bearing the Cos3p amino acid residues 94 -224 were overproduced in E. coli BL21 and purified by affinity chromatography with Ni-NTA-agarose (Qiagen) and glutathione-Sepharose beads (Amersham Biosciences), respectively (49). The purified Nha1p (C1ϩC2)-His and MBP-Cos3p-loop proteins were injected into rabbits to induce polyclonal antibodies.…”
Section: Analysis Of Protein-proteinmentioning
confidence: 99%
“…His tags were added to β subunits in order to precisely position and orient F 1 -ATPase molecules on nanofabricated substrates. Previous research demonstrated a 40% reduction in enzymatic activity associated with the addition of His tags to the F 1 -ATPase from E. coli (Ekuni et al 1998). For this reason, the mutated F 1 -ATPase constructs with and without His tags on the β subunit are currently being cloned into pQE-30, and expressed in E. coli JM103.…”
Section: F 1 -Atpase Biomolecular Motor Productionmentioning
confidence: 99%